Nomenclature and Classification of Odontogenic Tumors — Part II: Clarification of Specific Nomenclature. (December 2014) - Bell, Cynthia M.; Soukup, Jason W.
Accurate identification of odontogenic tumors is critical for productive communication and an important foundation for useful comparative epidemiologic studies of odontogenic tumors in both domestic animals and humans. This manuscript illuminates the subject of veterinary odontogenic tumor nomenclature and will serve as a foundation for future updates in nomenclature and classification of odontogenic tumors.